2008
DOI: 10.1152/ajplung.90352.2008
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant catalytic cycle and impaired lipid transport into intracellular vesicles in ABCA3 mutants associated with nonfatal pediatric interstitial lung disease

Abstract: However, the mechanisms underlying the less severe phenotype of patients with ABCA3 mutation are unclear. In this study, we characterized ABCA3 mutant proteins identified in pediatric interstitial lung disease (pILD). E292V (intracellular loop 1), E690K (adjacent to Walker B motif in nucleotide binding domain 1), and T1114M (8th putative transmembrane segment) mutant proteins are localized mainly in intracellular vesicle membranes as wild-type protein. Lipid analysis and sucrose gradient fractionation revealed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
74
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(83 citation statements)
references
References 39 publications
7
74
0
Order By: Relevance
“…To determine whether p.R288K and p.R1474W impair ATP hydrolysis (type II mutation), we extracted membrane protein from adenoviral-transduced A549 cells, performed a colorimetric ATPase assay, and compared results to a previously characterized ATP hydrolysis mutation, p.E292V (20). We found that, similar to p.E292V, both p.R288K (80% reduction, P , 0.0001) and p.R1474W (75% reduction, P = 0.0012) encoded ABCA3 proteins with significantly reduced ATPase activity compared with wild type (Figure 4).…”
Section: Atpase Assaymentioning
confidence: 99%
“…To determine whether p.R288K and p.R1474W impair ATP hydrolysis (type II mutation), we extracted membrane protein from adenoviral-transduced A549 cells, performed a colorimetric ATPase assay, and compared results to a previously characterized ATP hydrolysis mutation, p.E292V (20). We found that, similar to p.E292V, both p.R288K (80% reduction, P , 0.0001) and p.R1474W (75% reduction, P = 0.0012) encoded ABCA3 proteins with significantly reduced ATPase activity compared with wild type (Figure 4).…”
Section: Atpase Assaymentioning
confidence: 99%
“…Recessive loss-of-function mutations in ABCA3 present as lethal surfactant deficiency in the newborn, whereas other recessive mutations in ABCA3 can result in interstitial lung disease in older children [4]. Previous studies showed that homozygous or compound heterozygous ABCA3 mutations led to abnormal processing and/or trafficking of the ABCA3 protein [5], alterations in ABCA3 protein functions such as ATPase activity [6], or impaired lipid transport [7]. As previously described, our patient had a less severe phenotype than is usually associated with ABCA3 mutations [4].…”
Section: To the Editormentioning
confidence: 99%
“…34 , 35 The direct impact of an individual mutation on ABCA3 structure and function in relation to the clinical course has been determined for a small number of defi ned ABCA3 mutations. 36 When mutations associated with mild disease were expressed in vitro , the mutant ABCA3 protein was found to retain residual transport activity and acquire a subcellular localization similar to wild-type ABCA3. These results were interpreted to indicate retention of partial catalytic and transport function accounts for the mild disease.…”
Section: Neuroendocrine Cells and Diffuse Lung Diseasementioning
confidence: 99%